A new concept of speed amplified nonlinear electromagnetic vibration energy harvester through fixed pulley wheel mechanisms and magnetic springs. (1st July 2019) - Liu, Zhenwei; Wang, Xu; Ding, Songlin; Zhang, Ran; McNabb, Luke
Graphical abstract: Highlights: An innovative design of speed amplified electromagnetic oscillation energy harvester. Analysis of the harvester for its parameter study and performance optimization. A non-linear oscillator used for enhancing the performance through magnetic springs. Analytical/simulation method considering the rotational inertia of the pulley wheels. The dimensionless expressions of the output voltage and harvested power. Abstract: This paper proposes a novel design of speed amplified nonlinear electromagnetic vibration energy harvester through fixed pulley wheel mechanisms and magnetic springs. The new vibration energy harvester consisting of fixed pulley wheel mechanisms, nonlinear magnetic springs, inner and outer rectangular ring Halbach arrays of magnets and a four-phase coil connection has potential to generate more output voltage than that with the speed amplified linear electromagnetic vibration energy harvester and conventional non-speed amplified nonlinear electromagnetic vibration energy harvester. By so far no one has worked on increasing the relative speed of the magnets with respect to the coils by adopting the fixed pulley wheel mechanisms. The nonlinear vibration was achieved by adopting repulsive magnetic springs with nonlinear spring stiffness. Analytical and simulation solutions of the speed amplified nonlinear electromagnetic vibration energy harvester system considering the effects of the rotational inertia of the pulley wheels have been verified by experimental results. The dimensionless formulae of the relative displacement, output voltage and harvested power of the speed amplified nonlinear electromagnetic vibration energy harvester system have been established and experimentally validated.